Upaya Optimalisasi Media Promosi Melalui Pendampingan Usaha Untuk Ekspansi Pasar UMKM Di Kabupaten Tulungagung, Jawa Timur - Berlian Feby Wijayanti; Surya Duta Wiharsono; Ida Syamsu Roidah; Nuriah Yuliati (Lembaga Pengembangan Kinerja Dosen, 2024)
Micro, small and medium enterprises (MSMEs) play an important role in the Indonesian economy. Tulungagung Regency is one of the regions in East Java that has quite large MSME potential. Even though they have quite large income potential, MSMEs in Tulungagung also face a number of challenges such as a lack of knowledge among business actors regarding promotional media, use of technology, use of social media, as well as obstacles related to marketing and market access that does not reach many groups. One effective solution to overcome the obstacles faced by MSMEs is a business mentoring program, which enables MSMEs to acquire the knowledge and skills needed to design and implement effective promotional strategies. The data collection method uses primary data through interviews, observation, practice, and documentation and secondary data, using literature. The analysis used in mentoring MSMEs is a descriptive method with a qualitative approach in the form of descriptions and narratives complete with pictures and explaining conditions during mentoring MSMEs. Efforts to optimize promotional media through business assistance is a program used to help improve better promotional methods so that they can expand the marketing reach of MSMEs, especially in Tulungagung Regency. The flow of assistance carried out is, program introduction, delivery of material, implementation of promotional media practices, and closing. This activity was carried out in Tulungagung Regency, with a target of assisting 32 businesses every month. With this systematic approach, it is hoped that MSMEs can increase the visibility of their products, expand market reach, and build a strong brand identity. In addition, active participant participation and input from them also allows the program to continue to be improved and adjusted to be more effective in the future.